2009
DOI: 10.1161/circep.109.891440
|View full text |Cite
|
Sign up to set email alerts
|

α1-Syntrophin Mutations Identified in Sudden Infant Death Syndrome Cause an Increase in Late Cardiac Sodium Current

Abstract: Background-Sudden infant death syndrome (SIDS) is a leading cause of death during the first 6 months after birth. About 5% to 10% of SIDS may stem from cardiac channelopathies such as long-QT syndrome. We recently implicated mutations in ␣1-syntrophin (SNTA1) as a novel cause of long-QT syndrome, whereby mutant SNTA1 released inhibition of associated neuronal nitric oxide synthase by the plasma membrane Ca-ATPase PMCA4b, causing increased peak and late sodium current (I Na ) via S-nitrosylation of the cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 48 publications
2
72
0
1
Order By: Relevance
“…The exact molecular mechanisms underlying the loss of Na v 1.5 expression at the lateral membrane in the absence of dystrophin remains still unclear. Cheng and coworkers 33 recently described several mutations in the gene encoding ␣1-syntrophin in patients with sudden infant death syndrome. Despite these results, clearly demonstrating the importance of ␣1-syntrophin in cardiomyocytes function, our data suggest that this protein complex is restricted to the lateral membrane.…”
Section: Physiological Relevance Of the Two Regulating Mechanismsmentioning
confidence: 99%
“…The exact molecular mechanisms underlying the loss of Na v 1.5 expression at the lateral membrane in the absence of dystrophin remains still unclear. Cheng and coworkers 33 recently described several mutations in the gene encoding ␣1-syntrophin in patients with sudden infant death syndrome. Despite these results, clearly demonstrating the importance of ␣1-syntrophin in cardiomyocytes function, our data suggest that this protein complex is restricted to the lateral membrane.…”
Section: Physiological Relevance Of the Two Regulating Mechanismsmentioning
confidence: 99%
“…88 Finally, mutations in SNTA1 have also been linked to SIDS. 108 Ackerman and colleagues screened 292 SIDS cases, and identified 6 distinct SNTA1 mutations (p.G54R, p.P56S, p.T262P, p.S287R, p.T372M, and p.G460S) in 8 cases. Interestingly, when coexpressed with Na v 1.5 in HEK-293 cells, the p.G54R and p.P56S mutations did not affect I Na compared with wild-type SNTA1.…”
Section: Wilde and Brugadamentioning
confidence: 99%
“…Cheng et al (Cheng et al 2009) reported a mutation in α1-syntrophin (SNTA1) as a novel cause of long QT syndrome in sudden death infant syndrome (SIDS), and Tan et al (Tan et al 2010) suggested a mutation in the β subunit of the Na v 1.5 cardiac sodium channel as a cause of arrhythmia in SIDS. Mutations not only in ion channels but also in cardiac gap junction channels may cause conduction defects and lead to sudden death in children (SIDS).…”
Section: Channelopathiesmentioning
confidence: 99%